ANALISIS KONFLIK PENDIDIKAN SEBAGAI EVALUASI STANDAR PROSES DAN STANDAR PENILAIAN BERDASARKAN KURIKULUM 2013 - Made Adi Nugraha Tristaningrat (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
Technological advances have a major impact on human life, one of which is education.From these phenomena needed human resources capable of utilizing these developments. Interms of education, many changes occur both in terms of the educational process to the evaluationof the implementation of education. Many efforts have been done jointly by both governmentand school units in order to create resources capable of utilizing the development of availabletechnology. Developments in the world of education trigger every individual who moves in it tobecome more qualified so that the desired main goal will be more easily achieved. Can beexemplified in the world of education, technological developments trigger major changes in thecurriculum and development of educators. In its development, the curriculum has become animportant reference that can affect the learning process in the education unit. While in the realmof educator, technological development able to membarikan many supporting facilities in thelearning process in the classroom so that the educators more easily in carrying out their duties.Automatically, the developments that occur should be able to have a good standard of processand assessment standards so that it can really be well validated as well. In this case, the analysisis conducted with the objective of finding out early educational conflicts that may occur and toknow the right instruments in order to create careful preparation in case of anticipation of it. Ingeneral, this analysis is important in the effort to prepare human resources ready withtechnological developments.Keywords: Technology, Standar Process, Assessment Standar, Educational Conflicts